NATURAL ZEOLITES OF ARMENIA IN GEOECOLOGY (Proceedings of the YSU C: Geological and Geographical Sciences, 2007)
At present 40 species of natural zeolites and over 100 species of synthetic zeolites are known. In Armenia the massives of zeolite containing rocks (zeolitites) have a wide distribution. The properties of non-modificated, thermal-chemically modificated and treated with the rays of sample electrons of clinoptilolites in Noyemberyan deposit (Nor Koghb) are studied by experiments. Zeolites are characterized by great potential for application in industry, economy and geoecology.
Keywords: natural zeolites of Armenia; zeolitites; clinoptilolites; Nor Koghb; non-modificated; thermal-chemically modificated